Risk Factors Associated with Breast Cancer - Manuel Vargas-Hernández, Víctor (Journal of Hematology and Oncology Research, 2020)
In Mexico, breast cancer is the second most common site of cancer in women and in most developed and emerging countries. Incidence rates have increased in many countries, although in some, mortality has remained stable with a slight reduction. There are geographical differences with high rates of breast cancer in North America, Northern Europe and Oceania, and lower rates in Central and South America, South and East Europe; in addition to emerging countries in Africa and Asia. Genetic and hereditary factors constitute less than 5% of breast cancer cases and other risk factors for breast cancer are related to the reproductive life of the woman. This work was carried out in order to determine if the risk factors considered classic are really associated with breast cancer in our sample of Mexican women studied.
Keywords: Breast Cancer; Risk Factors; Genetic and Hereditary Factors; Incidence Rates; Mexican Women